Fundamentos do conhecimento científico para a formação humana em Theodor Adorno e Max Horkheimer​ - Bernardes, Giselle Carvalho (2023)
The aim of this thesis was to reveal the foundations of formative scientific knowledge in Theodor Adorno (1903-1969) and Max Horkheimer (1895-1973), authors of the Critical Theory of Society, also known as the Frankfurt School. This is a theoretical research carried out from the analysis of the texts: “The concept of enlightenment” and “Excurso I: Ulisses or myth and Enlightenment”, both from 1947, “Semi-formation theory”, from 1959, “Education - what for?”, from 1966, “Education after Auschwitz”, from 1967, “Education against barbarism”, from 1968, “About subject and object”, from 1969, “Marginal notes on theory and praxis”, 1969, “Traditional Theory and Critical Theory”, from 1937, and “Means and Ends”, from 1941. From the analysis of the debates carried out by the authors in the interweaving between knowledge, reason and formation, the categories “Contradiction”, “Reason reflexive criticism”, “Primacy of the object”, “Articulation between whole and part, universal and particular” and “Theory and praxis”, which establish relationships towards the constitution of a knowledge that resists instrumental reason, capable of guiding training for emancipation. Thus, it is concluded that for the two authors there is a certain type of scientific knowledge that is linked to human formation.